Factors affecting consumer purchasing intention : a study of online shopping in Bangladesh - Nayeem, Abdur Rakib (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
Online shopping has become more popular and important avenue for organizations as they face fierce competition. Also, the growing utilization of internet among the youth in Bangladesh has given a rising prospect to the online sellers. In the event that online sellers are aware of the factors influencing Bangladeshi buyers' purchasing intention and the relationship between these factors and online purchasers; they can build up their selling systems to change their potential clients to dynamic ones. Based on this view, four key measurements of web based shopping as seen by young buyers in Bangladesh are distinguished. In addition, the researcher also investigates whether there are distinctions in online shopping by various groups of consumers in Bangladesh. As such, convenience sampling method was used to collect quantitative data from 230 customers with greater experiences in online shopping in Bangladesh. Moreover, data collected was analyzed using correlation and multiple regressions with the help of SPSS software. It was found that attitude, subjective norms, perceived behavior control, website design, and trust are the five key factors which have positive and significant impact on online purchasing intention. However, there is no significant difference between different stages of customers on web based shopping conducted in Bangladesh. The researcher is of the opinion that the suggestions offered in this study would encourage the development of Bangladeshi online transactions.